Oral plasmablastic lymphoma: at the origin of the discovery of an HIV infection - Rahman Nurhayu Ab; Hussain Faezatul Arbaeyah; Eng Kam Chuan (Journal of Oral Medicine and Oral Surgery)
Introduction: Plasmablastic lymphoma is a rare and aggressive malignancy derived from a B cell lineage. It has a predilection for extranodal sites, particularly arises de novo in the oral cavity. Underlying immune deficiency is a well-established factor, as most cases are associated with HIV infection or posttransplant patients. Observation: A 55-year-old man presented with a large, painful, multi-lobulated, bluish-purplish mass on the right posterior maxillary gingiva and was initially misdiagnosed as a dental abscess. He was married with three children and had no known risk for immune deficiency. The histopathological diagnosis revealed a plasmablastic lymphoma lesion, which subsequently led to the establishment of the patient's HIV positive status. Conclusions: From a histopathology perspective, HIV testing is warranted in a patient who has been diagnosed with plasmablastic lymphoma despite having a negative history of HIV, transmission risk or exposure to further establish the clinicopathological correlation. Clinically, this testing is necessary to determine the patient's overall therapy, with a focus on counselling of the individual patient and family members to prevent the disease from spreading further.